2015
DOI: 10.1055/s-0035-1556731
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and Hemorrhage in Diabetic Retinopathy: A Perspective from an Inflammatory Standpoint

Abstract: Retinal ischemia and hemorrhage are hallmarks of worsening diabetic retinopathy, which can lead to neovascularization, macular edema, and severe vision loss. Although diabetes alters expression of clotting factors and their activities, and increases retinal microthromboses, the effects of thrombotic processes on the pathogenesis of diabetic retinopathy are not fully understood. In addition to the roles of coagulation and fibrinolytic cascades in thrombosis and hemostasis, components in these systems also media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…TM, via thrombin-mediated activation of protein C and TAFI, provides protection against inflammation. Thrombin is an important inflammatory factor in retinal vascular diseases including DR 41 . It was reported that thrombin and prothrombin were increased in the vitreous of patients with proliferative DR compared with nondiabetic individuals 42 .…”
Section: Discussionmentioning
confidence: 99%
“…TM, via thrombin-mediated activation of protein C and TAFI, provides protection against inflammation. Thrombin is an important inflammatory factor in retinal vascular diseases including DR 41 . It was reported that thrombin and prothrombin were increased in the vitreous of patients with proliferative DR compared with nondiabetic individuals 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides inflammation and apoptosis, platelet adhesion is also involved in diabetes-induced retinal endothelial dysfunction 93 . The platelet adhesion to the injured diabetic endothelium takes part in ischemia and inflammation, both coagulation and fibrinolytic cascades in the vitreous are identified in DR 114 . Blood platelets tend to adhere to the vascular endothelium of DR rather than normal vessels 115 , which is involved in retinal capillaries occlusion and microvascular damage.…”
Section: Generation Of H2s In Ocular Tissuesmentioning
confidence: 99%
“…More than 50% of patients with diabetes experience retinopathy, of which 1%–2% become blind as a result (Moraes & Layton, 2016). The pathogenesis of DR remains unclear, however, several studies have implicated apoptosis, inflammation, and oxidation (Mrugacz & Bossowski, 2016; Murugesan et al., 2015; Tong et al., 2019).…”
Section: Introductionmentioning
confidence: 99%